2015
DOI: 10.1038/srep13630
|View full text |Cite
|
Sign up to set email alerts
|

High expression of SOX30 is associated with favorable survival in human lung adenocarcinoma

Abstract: In our previous study, we had identified SOX30 as a novel tumor suppressor that acts through direct regulation of p53 transcription in human lung cancer. Here, we sought to determine the clinical relevance of SOX30 expression in a series of surgically-resected non-small cell lung cancer (NSCLC) patients. Analysis of SOX30 expression and clinico-pathologic features reveal a significant correlation of SOX30 expression with histological type (n = 220, P = 0.008) and clinical stage (n = 220, P = 0.024). Kaplan-Mei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 33 publications
0
38
0
Order By: Relevance
“…Our data showed that LHX6 expression was a favorable prognostic factor in lung adenocarcinoma but not in lung squamous carcinoma patients. Recent studies have reported that SOX30 was a favorable prognostic factor in lung adenocarcinoma but an unfavorable one in lung squamous carcinoma 8 , and GPC5 was also found to be related to the clinical progression only in lung adenocarcinoma patients 9 . Furthermore, our clinical study suggested that LHX6 was an independent prognostic factor for lung adenocarcinoma patients and for patients with negative lymph node status.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our data showed that LHX6 expression was a favorable prognostic factor in lung adenocarcinoma but not in lung squamous carcinoma patients. Recent studies have reported that SOX30 was a favorable prognostic factor in lung adenocarcinoma but an unfavorable one in lung squamous carcinoma 8 , and GPC5 was also found to be related to the clinical progression only in lung adenocarcinoma patients 9 . Furthermore, our clinical study suggested that LHX6 was an independent prognostic factor for lung adenocarcinoma patients and for patients with negative lymph node status.…”
Section: Discussionmentioning
confidence: 99%
“…The tissues were stained with hematoxylin-eosin and then reviewed histologically by at least two pathologists. Finally, the TMAs were constructed (in collaboration with Shanghai Biochip Company Ltd, Shanghai, China) as previously described 8 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tumor cell staining was considered positive when immunoreactivity was greater than or equal to 10%. Positive staining was divided into 5 categories, and staining intensity was graded according to 4 levels as previously described [25]. The expression levels were defined by the sum of positive staining and intensity.…”
Section: Methodsmentioning
confidence: 99%